KLK2 single-nucleotide polymorphism rs198977 is associated with increased susceptibility and hyperleukocytosis in AML - Meng, Guangqiang; Li, Peng; Li, Mingying; Wu, Yuyan; Ma, Yuechan; Sun, Tao; Ji, Chunyan (Frontiers in Genetics, 2023)
Acute myeloid leukemia (AML) is a heterogeneous myeloid malignancy with abnormal molecular diversity. Tissue kallikrein 2 (KLK2) is a kind of serine protease, and has a close relationship with the occurrence and development of malignant tumors. Single nucleotide polymorphism (SNP) of various genes are associated with susceptibility, treatment and survival of AML. Here, we investigated the association of KLK2 SNPs rs198977 and rs2664155 with AML. We recruited 284 AML patients and 280 healthy controls from the Han population and genotyping KLK2 SNPs rs198977 and rs2664155 by MassARRAY system. Using clinical data from AML patients and controls, including AML susceptibility, blood count, risk stratification, response to induced chemotherapy and survival, our results showed an increased risk of AML susceptibility with KLK2 rs198977 TT genotype in the recessive model. Regarding white blood cell counts in AML patients, the results showed an increased risk of hyperleukocytosis with the TT genotype of KLK2 rs198977 in a codominant model. Moreover, in the recessive model, AML with KLK2 SNPs rs198977 TT genotype had an increased risk of hyperleukocytosis. No significant correlation was found between KLK2 rs2664155 and AML. This study suggests that KLK2 rs198977 may be an important genetic factor in the occurrence of AML and hyperleukocytosis in AML, providing a new perspective for disease progression and new therapeutic targets.